CONSTRUCTION OF MUSHALLA AND AL-QUR'AN EDUCATION PARK (TPA) DEPOK CITY: PEMBANGUNAN MUSHALLA DAN TAMAN PENDIDIKAN AL-QUR’AN (TPA) KOTA DEPOK - Muji Indarwanto; Sarjono Puro; Edison Hatoguan Manurung (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2021)
In order to improve the function of the Mosque in this case, mushalla as a place of worship and the construction of the people in particular, where people's lives are so compound and crowded, and to increase piety in performing worship (congregational prayer) as best as possible, prospering the Mosque has a positive influence for the development of the community in order to improve the quality of life of the community and the country. In order for religious syi'ar to be more echoed because it requires some improvement because of the inadequate physical condition of the building, it is necessary to renovate the construction of Mushalla and Al-Qur'an Education Park (TPA) which is regressive, is a program of mushalla management in Curug Village, RT.06 RW.04, Bojongsari Subdistrict, Depok City, West Java for the creation of a solemn and comfortable atmosphere of worship. The activities began with a coordination meeting with mushalla administrators in Curug Village, RT.06 RW.04, Bojongsari Subdistrict, Depok City, West Java, and residents around the Mosque, planning, drafting, and calculation in the making of Unit Price Analysis (AHS) in order to be analyzed and carried out on time. Mushalla is a center of community activities and development. And besides that, we should be able to position the Mosque as a unifying forum for Muslims